Coffee bean chemical and qualitative characterization from three producers regions of Minas Gerais - Chagas, Sílvio Júlio de Rezende; de Carvalho, Vânia Déa; Costa, Laerte (Pesquisa Agropecuaria Brasileira, 1996)
This work was carried out with the objetive of characterizing coffee from 18 counties of the three principal regions of Minas Gerais, Brazil, for quality and chemical components, as well as to relate the parameters to the final product quality. Coffee samples harvested by stripping coffee berries from the branches into a piece of cloth were used. Each sample was made up of nearly 4 kg of coffee berries. Araguari, Coromandel and Patrocínio counties in the Trifingulo Mineiro/Alto Paranaiba regions; Três Pontas and Boa Esperança in the South of Minas Gerais and, Divino in the Zona da Mata region were found to produce coffee of the best quality, which showed a high poliphenoloxidasis activity and higher color level.